Induna Cave, southeastern Zimbabwe: a record of a 'contact period' assemblage in a changing landscape - Thorp, C. (Southern African Humanities, 2010)
Excavation of Induna Cave in the southeastern lowveld of Zimbabwe has established that stone tool-using hunter-gatherers occupied the site until at least the late twelfth century AD. Relatively formal stone-artefact assemblages together with ceramics came from two contact-period levels. These assemblages suggest either occupation of the cave by hunter-gatherers using items of material culture acquired from farmers who were living in close proximity to the site, or alternate use by farmers and hunter-gatherers. An earlier stone-artefact assemblage with few formal tools and some ceramics, possibly displaced from the contact-period occupation above, may represent either a pre-contact or a contact occupation of the site, which was probably used as a hunting camp and a place for processing ostrich eggshell beads at this time. A small pre-ceramic assemblage shows that the area was occupied by hunter-gatherers before farmers arrived in the region.